The Assessment of Validity Test on Hypertension Screening Instrument - Carine Ryan Amala (Universitas Airlangga, 2018)
Background: Hypertension is the cause of death with high prevalence of 6.80% for all age groups. One of the efforts that can be fone in order to control the hypertension incidence is developing and supporting the early detection with good validity. Purpose: This study aimed to assess the validity of hypertension screening instrument and give suggestions related to the findings. Methods: The hypertension screening instrument that was used in this study was questionnaire related to clinical symptoms and risk factors. Results: There were 15 respondents (36.60%) from 41 respondents reported to have hypertension. Meanwhile, there were 21 respondents (51.20%) based on tensimeter assessment as the gold standard suffered from hypertension. Furthermore, validity test results showed high sensitivity (71.43%), specificity (100%), positive prediction (100%), and negative prediction (76.92%). The weaknesses of the instruments were found in the inappropriate suggestion, improper procedures of blood pressure measurement according to Operational Standard Procedure. Data obtained from elder respondents (aged above 50 years old) can influence the validity of measurement result. Conclusion: The validity index of the screening instrument was high, but it was not designed to be applied widely for screening as there were weaknesses in the process.